Factors Influencing SARS-CoV-2 Vaccine Acceptance and Hesitancy in a Population-Based Sample in Italy - Marco Del Riccio; Sara Boccalini; Lisa Rigon; Massimiliano Alberto Biamonte; Giuseppe Albora; Duccio Giorgetti; Paolo Bonanni; Angela Bechini (Vaccines, 2021)
Vaccination against SARS-CoV-2 represents an effective and safe tool to protect the population against the disease; however, COVID-19 vaccine hesitancy could be a major barrier to achieving herd immunity. Despite the severity of the current pandemic, the population’s intention to get vaccinated against COVID-19 is still not clear. The aim of this study was to evaluate the intention to get vaccinated against COVID-19 among a convenience sample of the general population resident in Italy and the factors associated with hesitancy and acceptance of the vaccine in the context of the current pandemic before the rolling out of COVID-19 vaccines. An anonymous online survey was diffused among a general adult population living in Italy. Participants aged 18 or older and living in Italy were considered eligible. Incomplete questionnaires were excluded. Overall, 7605 valid questionnaires were collected. Most of the participants (81.9%) were inclined to get vaccinated; male sex (OR 1.38, 95% CI 1.12–1.71), a high level of trust in institutions (OR 3.93, 95% CI 2.04–7.83), and personal beliefs about high safety of COVID-19 vaccines (OR 56.33, 95% CI 31.57–105.87) were found to be among the significant predictors of COVID-19 acceptance. These data could help design larger studies to address the problem of COVID-19 vaccine hesitancy in the current pandemic.